Penerapan Model Pembelajaran Flipped Learning Dalam Meningkatkan Hasil Belajar Siswa - Asmaul Husna; Sakdiyah; Rahajam; Musfiana; Raihani (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
The aim of this research is to determine the effect of the Flipped Learning learning model on student learning outcomes. This study uses a quantitative approach with a pre-experimental research type. Data collection techniques in this study were using tests, questionnaires, and documentation. While the data analysis technique was the t-test. The results of the study showed that there were differences in student learning outcomes before and after the Flipped Learning learning model was implemented, this can be seen from the t_count value of 11.768 and the sig. value. The results obtained were 0.000 or 0.000 <0.05, so Ho was rejected and Ha was accepted. The results of the student response questionnaire were 91%, which means that the results are included in the very good category. Researchers recommend that schools, especially teachers, prepare a summary of the material in the form of a printout that can be directly distributed to students if there is a power outage. With this alternative, learning activities can continue even though there are technical constraints.